Analysis of clinical and genetic characteristics of 18 pediatric patients with Barth syndrome - ZHAN Tianliu; YAN Zihang; WU Jinjin; CHEN Hao; CHEN Lijun; CHEN Yiwei; FU Lijun (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To analyze the clinical and genetic characteristics of Chinese pediatric patients with Barth syndrome (BTHS) and provide data to support the prevention and treatment of BTHS.Methods·Eighteen pediatric patients diagnosed with BTHS at Shanghai Children′s Medical Center, Shanghai Jiao Tong University School of Medicine, from January 2010 to November 2023, were included. Clinical data (age, birth weight, family history, electrocardiogram, echocardiogram, urine tandem mass spectrometry, complete blood count, blood biochemistry, and genetic test results) were collected to analyze the clinical characteristics, genetic findings, and prognoses of the patients.Results·The study included 18 male patients with BTHS (including 2 monozygotic twins), consisting of one Yi ethnic and 17 Han Chinese patients. The median age at diagnosis was 3.0 (1.0, 5.6) months. Fifteen patients experienced decreased cardiac function at disease onset, with a left ventricular ejection fraction (LVEF) below 50%. Dilated cardiomyopathy (DCM) was observed in 15 patients, left ventricular non-compaction (LVNC) in 12 patients, and myocardial hypertrophy in 9 patients. During the diagnosis and follow-up, QTc interval prolongation occurred in 9 patients, ventricular arrhythmias in 2 patients, neutropenia in 9 patients, and monocytosis in 10 patients. Urine tandem mass spectrometry revealed 3-methylglutaconic aciduria (3-MGCA) in 8 of 13 tested patients. Fifteen types of TAZ gene mutation were identified in the 18 patients, including 5 novel mutations. Genetic testing of the parents of 16 patients indicated maternal inheritance in 15 cases. The median follow-up period was 8.5 (2.6, 29.3) months, during which 12 patients died. The median age at death was 7.5 (6.0, 12.8) months. Causes of death included heart failure (7 cases, with 4 concurrent infections), sudden death (3 cases), ventricular fibrillation (1 case), and accidental death (1 case).Conclusion·BTHS is a rare genetic disorder with multisystem involvement. Its primary clinical manifestations include cardiomyopathy and neutropenia. The condition typically presents early in life, with severe progression and poor prognosis. Prompt recognition, accurate diagnosis, and early intervention are essential for managing this disease.